Aphorisms & quotations for the surgeon - Schein, Moshe (Tfm Pub., 2003)
This book brings together a medley of over 1500 aphorisms, quotations, and rules - by surgeons and non-surgeons - about surgery, surgeons and anything which may be relevant to the practice of surgery. It should gratify all potential tastes as the book includes ancient as well as contemporary entries, formal and colloquial, pronounced by surgical giants or anonymous - only guided by the prerequisite that the entry appeals to the surgical soul.